Symposium on the Buchanan Report - Northcott, Jim; Ryan, Pierce; Ryan, Liam (Statistical and Social Inquiry Society of Ireland, 1970)
The aim of the regional development studies was to work out a strategy for regional development which would offer the best possible prospects of achieving the aim of a full employment society, equated in the National Industrial Economic Council's Report on Full Emplovment, with bringing unemployment down to 2% and net emigration down to 5,000 a year. The first step was to prepare some basic forecasts on the one hand of potential future population and the number of people likely to be wanting jobs, and on the other, of the number of jobs in each of the main economic sectors likely to be actually available
Read before the Society, 1 May 1970
Keywords: Buchanan report; Regional development; Growth centres; Land use; Rural development; 314.15